(untitled) (Research, Society and Development, 2020)
The word Fanatic is derived from Latin, and its meaning is temple, sanctuary. This explains the fact that the fanatic unconditionally serves what he considers the greatest, indisputable. This term also underwent modifications, initially linked to the devotion and worship of several gods, with the passage of time it is attributed to a single cause or better specifying, a single belief. Thus, the main objective of this article is to discuss the implications of fanaticism in different social contexts today through the contribution of Psychoanalysis. The study was carried out through a qualitative bibliographic search, by means of content analysis. For this purpose, books, articles and thesis were used that address the theme of fanaticism. The search for scientific articles on the subject occurred during the first half of 2020, through the electronic database Google Scholar, Scielo e Pepsic. It was found that similar characteristics of that subject who lose control over his acts, considered dysfunctional fanatic, ind different social context. Among them, aggressiveness, the lack of the ability to laugh at oneself, violence and believing that only your opinion has value. Finally, it is concluded that parents are extremely influential in children’s choices and some fanatical characteristics appear as a parental inheritance.